Design and development of an electric vehicle battery cooling system - Gundran, Julius Ezra M. (Animo Repository, 2019)
Jeepneys are a chief component of the Philippine transport system, as well as a chief contributor of harmful air pollutants. This, among an array of other issues with public transport has led the government to launch the Public Utility Vehicle Modernization Program, a key component of which is the adoption of technologically and environmentally superior alternative technologies such as electric jeepneys. Electric jeepneys suffer from a significant drawback – its short battery life, which greatly contributes to the vehicle’s maintenance costs and decreases its adoption. A highly effective solution to this is the battery cooling system, which has been shown to significantly extend battery life. This study hence aims to: develop a system model describing the electrical and thermal behavior, aging, and cooling system of its battery, select a battery cooling system design suitable to a typical electric jeepney, determine the optimal balance between capital, operating, maintenance and associated battery replacement costs of the cooling system, and fabricate the designed cooling system and test the response of the battery. The optimization of the design is implemented in a mathematical/simulation software, coupled with the developed system model. The system simulation uses operational profiles patterned after actual jeepney operation. The net present costs of two design choices, an active air-cooled and passive PCM-cooled one, are minimized using a genetic algorithm, paired with a system simulation covering the electrical, thermal and aging behavior of the battery. Two cases are also explored – operation under a drive cycle and under discharge at 3C, representing routine and extreme use. It is determined that for routine use, having no cooling is still the most economical choice, and that for extreme use, PCM cooling is the most advantageous option, both in terms of temperature reduction and cost. Lastly, the designed cooling system is fabricated. State of health (SOH) tests were conducted for cells under three cases – uncooled at 40 °C ambient, cooled at 40 °C ambient, and uncooled at room temperature. It was found that the higher-temperature cells have a slight advantage in terms of charging and discharging voltage and capacity. The cooled cells also have a significantly lower temperature rise and peak temperature than the uncooled cells at 40 °C ambient. However, the SOH results show that the cooled cells have no significant improvement in terms of SOH reduction. Also, the room temperature cells, which had the highest temperature rise of all cases, were found to have the greatest SOH reduction.